Electrophysical beam technologies in vegetable growing: synergetic action of physical and chemical factors - Базалєєв, М.І.; Духін, Є.О.; Клепіков, В.Ф.; Литвиненко, В.В.; Могильна, О.М.; Молчанов, Ю.А.; Набока, О.М.; Шаляпін, С.М.; Яровий, Г.І. (Eastern-European Journal of Enterprise Technologies, 2010)
The regularities of wide interval doze ultraviolet treatment on cucumbers and table beets cultivation sprouting and grows were studied. The multifactors experiments which conclude in ultraviolet, microelement and growing regulators treatments were done. It is established the positive results of complexes influence of physical and chemical factors.